Depression and alcohol withdrawal syndrome: is antidepressant therapy associated with lower rates of hospital readmission?. (August 2016) - Schoonover, K.; Burton, M.; Larson, S.; Cha, S.; Lapid, M.
Abstract Background Alcohol withdrawal syndrome (AWS) is a frequent cause of admission to acute care hospitals and many of these patients have a history of depression. Aim Our objective was to determine if antidepressant use in patients with a history of depression is associated with lower rates of hospital readmission for AWS. Methods A retrospective study was performed of patients admitted with AWS between January 1, 2006 and December 31, 2008 to an academic tertiary referral hospital. Results Three hundred and twenty-two patients were admitted with AWS during the study period. One hundred and sixty-one patients (50 %) had no history of depression, 111 patients (34 %) had a history of depression and antidepressant use, and 50 patients (16 %) had a history of depression and no antidepressant use. There was no significant difference in the number of hospitalizations for AWS between these three groups. Patients with a history of depression on antidepressant medication were more likely to be retired or work disabled compared to the other two groups (p < 0.05). The antidepressant class most commonly used was SSRI (63 %). Conclusion Our study highlights the high frequency of depression and antidepressant use in patients admitted with AWS to an acute care hospital. As alcohol withdrawal is associated with increased morbidity and mortality and depression is common in those with alcohol use disorder, further research is necessary to clarify the optimal treatment of comorbid depression and alcohol use disorder in reducing these revolving door admissions.